Enhancing drought resilience: evaluating the livelihood outcomes of a solar-powered water system in Hanzila Village, Southern Zambia - Mweemba, Carol; Amarnath, Giriraj; van Koppen, Barbara (International Water Management Institute, 2025)
Increasingly severe and frequent droughts significantly affect livelihoods, agriculture, and water security in Zambia, particularly in the Southern Province. In response, the ACTION Grant Program collaborated with the Ministry of Agriculture and the Monze Town Council to implement a locally led initiative to build resilience against droughts in the Hanzila community of Monze district. The project emphasized community participation, from inception until completion, to create locally tailored and sustainable solutions. This led to the installation of a multi-purpose solar-powered borehole in September 2023, providing water for drinking and domestic use, irrigation, and livestock through ten strategically located taps.